Proses Produksi Konten Edukasi Praktek Pencegahan Pungutan Liar (PUNGLI) Komite Di Sekolah Menggunakan Media Sosial Ombudsman Republik Indonesia Perwakilan Provinsi Sumatera Barat - ., Martaliza; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The production of this educational content is motivated by the committee collecting money associated with students' academic affairs. Meanwhile, based on Article 10 Regulation of the Minister of Culture, that committees in fundraising only in the form of assistance and donations. Therefore, the author and his team did this the committee's process of producing educational content on illegal levies so that in practice they do not maladministration occurred. This educational content production is aimed at parents students can understand the context of the committee in accordance with the agreed rules, and be able to differentiate between things that fall into the category of illegal levies school environment. This educational content is disseminated to the public via The official social media of the Indonesian Ombudsman Representative of West Sumatra Province, namely Instagram. The process of content production activities begins with a discussion of ideas and cases which will be included in educational content, including taking videos at three predetermined locations. After completing the educational content The editing process was then uploaded to the Indonesian Ombudsman's Instagram social media Representatives of West Sumatra Province, an evaluation was carried out on use subtitles (dubbing) which should be in Indonesian.